Engaged Fatherhood for Men, Families and Gender Equality Healthcare, Social Policy, and Work Perspectives - Grau Grau, Marc.; las Heras Maestro, Mireia; Riley Bowles, Hannah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This aim of this open access book is to launch an international, cross-disciplinary conversation on fatherhood engagement. By integrating perspective from three sectors$1 (BHealth, Social Policy, and Work in Organizations$1 (Bthe book offers a novel perspective on the benefits of engaged fatherhood for men, for families, and for gender equality. The chapters are crafted to engaged broad audiences, including policy makers and organizational leaders, healthcare practitioners and fellow scholars, as well as families and their loved ones. .s
1 Launching a Cross-Disciplinary and Cross-National Conversation on Engaged Fatherhood -- 2 The Role of Fathers in Child and Family Health -- 3 The Impact of Father$1 (Bs Health on Reproductive and Infant Health and Development -- 4 The Impact of Fatherhood on Men$1 (Bs Health and Development -- 5 Steps in Developing a Public Health Surveillance System for Fathers -- 6 Fatherhood and Reproductive Health in the Antenatal Period: From Men$1 (Bs Voices to Clinical Practice -- 7 Fathers and Family Leave Policies: What Public Policy Can Do to Support Families -- 8 Individual Parental Leave for Fathers - Promoting Gender Equality in Norway -- 9 How do Men Talk about Taking Parental Leave? Evidence from South Korea, Spain and the U.S -- 10 Impossible Standards and Unlikely Trade-Offs: Can Fathers Be Competent Parents and Professionals -- 11 The New Dad: The Career-Caregiving Conundrum -- 12 French Fathers in Work Organizations: Navigating Work-Life BalanceChallenges -- 13 It would be silly to stop now and go part-time: Fathers and Flexible Working Arrangements in Australia -- 14 Small Changes that Make a Great Difference: Reading, Playing and Eating with Your Children and the Facilitating Role of Managers in Latin America -- 15 Fatherhood Among Marginalised Work-Seeking Men in South Africa -- 16 The Role of Love & Children$1 (Bs Agency in Improving Fathers Wellbeing -- 17 Reducing Barriers to Engaged Fatherhood: Three Principles for Promoting Gender Equity in Parenting.s
Keywords: Personnel management; Social policy; Business; Management science; Identity politics; Economics; Culture; Human Resource Management; Social Policy; Business and Management; Human Resource Management; Politics and Gender; Cultural Economics